Hospital Enterprise Architecture Design Using EA3 Cube Framework - Cosmas Samuel Daeli; Erwin Setiawan Panjaitan; Roni Yunis (INFOKUM, 2022)
Along with the times and the expansion of Information Technology (IT) in the increasingly significant business world competition, the company faces new challenges so that the company and business strategy changes significantly. A company that still wants to be modern, Enterprise Architecture (EA) must be a priority and enterprise modeling is a new field that continues to get attention and one of the frameworks that is currently widely used in describing the architecture of an enterprise is the EA3 Cube Framework.